High-temperature-resistant building ceramic tile and preparation method thereof

By using modified clay and other high-efficiency materials to prepare ceramic tiles and spray modified polysiloxane, the problems of insufficient heat resistance and poor self-cleaning ability of ceramic tiles in high-temperature environments are solved, and the high temperature resistance and self-cleaning properties of ceramic tiles are significantly improved.

CN119735425AActive Publication Date: 2025-04-01YUNFU HUIPENG CERAMICS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411831314.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-01
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

Existing ceramic tiles have insufficient heat resistance in high temperature environments and are difficult to clean themselves in environments with a lot of rainwater and dust, which affects the beauty and service life of the building.

Method used

Modified clay, magnesium trisilicate, titanium carbide, zirconium diboride, alumina, boron nitride and other materials are mixed and ground and pressed into a blank. After drying and sintering, modified polysiloxane is sprayed to improve the high temperature resistance and self-cleaning properties of ceramic tiles.

Benefits of technology

The high temperature resistance of ceramic tiles is significantly improved, and good self-cleaning performance is achieved through the hydrophobic layer of modified polysiloxane, which extends the service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant building ceramic tile and a preparation method thereof, and relates to the technical field of ceramics. When the high-temperature-resistant ceramic tile for the building is prepared, firstly, vinyl amino-terminated silicon oil reacts with 2-amino-4-pyridine methyl mercaptan, and then reacts with 2-(diphenylphosphine) benzaldehyde to obtain modified polysiloxane; secondly, mixing clay and the mixed ferric salt solution, and coprecipitating under the action of sodium hydroxide to obtain modified clay; finally, the modified clay, magnesium trisilicate, titanium carbide, zirconium diboride, aluminum oxide and boron nitride are mixed, ground and pressed into a blank, the blank is dried and sintered, modified polysiloxane is sprayed, and the high-temperature-resistant building ceramic tile is obtained. The high-temperature-resistant building ceramic tile prepared by the invention has good high-temperature resistance and self-cleaning performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, in particular to a high-temperature resistant building ceramic tile and a preparation method thereof. Background Art

[0002] Ceramic tiles are a new type of roofing material, widely used in the roofs and walls of civil buildings such as houses, villas, apartments, etc., as well as the roofs and walls of industrial buildings such as factories, warehouses, workshops, etc. However, existing ceramic tiles still have some shortcomings. For example, the high temperature resistance of ceramic tiles may not be optimal. In an environment with more rain and dust, ceramic tiles need to have the ability to self-clean in order to maintain the beauty of the building and extend its service life. Summary of the invention

[0003] The object of the present invention is to provide a high temperature resistant building ceramic tile and a preparation method thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] The invention discloses a high temperature resistant building ceramic tile, which is obtained by mixing and grinding modified clay, magnesium trisilicate, titanium carbide, zirconium diboride, aluminum oxide and boron nitride, pressing them into blanks, drying and sintering them, and then spraying them with modified polysiloxane.

[0006] Preferably, the modified polysiloxane is obtained by reacting vinyl-terminated amino silicone oil with 2-amino-4-pyridinemethyl mercaptan, and then reacting with 2-(diphenylphosphine)benzaldehyde.

[0007] A method for preparing a high temperature resistant ceramic tile for construction, comprising the following preparation steps:

[0008] (1) octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane are mixed in a mass ratio of 4:1, heated to 80°C, 0.02-0.03 times the mass of octamethylcyclotetrasiloxane is added with a 25wt% tetramethylammonium hydroxide aqueous solution, then heated to 100°C, 0.01-0.02 times the mass of octamethylcyclotetrasiloxane is added with 1,3-bis(aminopropyl)tetramethyldisiloxane, then heated to 115°C, reacted for 6h, further heated to 140°C, reacted for 40min, then cooled to 135°C and distilled under reduced pressure to obtain vinyl-terminated amino silicone oil;

[0009] (2) vinyl-terminated amino silicone oil, 2-amino-4-pyridinemethyl mercaptan, azobisisobutyronitrile and anhydrous toluene are mixed in a mass ratio of 1: (4.1-4.2): (0.1-0.3): (10-12), and the mixture is heated to 100° C. in a sealed, anhydrous and oxygen-free environment under an argon atmosphere, and reacted for 2 hours. After cooling to room temperature, a 1 mol / L sodium bicarbonate aqueous solution of 4-5 times the volume of anhydrous toluene is added, and extracted with ethyl acetate, and the organic phase is washed 3-4 times with a 1 mol / L sodium bicarbonate aqueous solution, and then washed with pure water for 3-4 times. Finally, the pre-modified polysiloxane is obtained by rotary evaporation at 80° C. for 5-10 minutes;

[0010] (3) Weighing pre-modified polysiloxane and 2-(diphenylphosphine)benzaldehyde in a mass ratio of 1:(3-3.5), mixing pre-modified polysiloxane, potassium carbonate, and N,N-dimethylformamide in a mass ratio of 1:(3-3.5):20, heating to 90-100° C. and stirring for 3-4 h to obtain a pre-modified polysiloxane solution, and mixing 2-(diphenylphosphine)benzaldehyde and N,N-dimethylformamide in a mass ratio of 1:20 to obtain 2-(diphenylphosphine)benzaldehyde. solution, adding the 2-(diphenylphosphine)benzaldehyde solution to the pre-modified polysiloxane solution at a dropping speed of 1 mL / min, continuing to react at 90-100°C for 3-4 hours after the dropping is completed, cooling to room temperature, adding pure water 10-12 times the mass of the pre-modified polysiloxane, cooling to 0°C and standing for 2-3 hours, adding acetone 3-4 times the mass of the pre-modified polysiloxane solution, filtering and drying at 50-60°C for 12 hours to obtain modified polysiloxane;

[0011] (4) mixing clay and pure water at a mass ratio of 3:10 to obtain a clay dispersion, mixing a mixed iron salt solution and a clay dispersion at a mass ratio of 1:(2-3) for 5-10 minutes, adding a 10M sodium hydroxide solution of 3-4 times the mass of the mixed iron salt solution, stirring at a speed of 100-200 r / min for 60 minutes, preparing a raw material ball with a particle size of 5 mm, and drying the raw material ball at 267 Pa and 90° C. for 12 hours to obtain a modified clay;

[0012] (5) Weigh the following raw materials by mass: 28-33 parts of modified clay, 7-11 parts of magnesium trisilicate, 9-14 parts of titanium carbide, 11-15 parts of zirconium diboride, 3-5 parts of aluminum oxide, and 3-4 parts of boron nitride; mix the above raw materials and grind them in a ball mill to obtain powder. The speed of the ball mill is 200 rpm / min, and the grinding time is 6 hours. Pour the powder into a mold and use a press to form a blank. The press pressure is 50 tons. The blank is placed in a dryer at a temperature of 280°C and dried. After drying, it is sintered in a high-temperature furnace to obtain a ceramic tile precursor; spray the modified polysiloxane on the surface of the ceramic tile precursor and dry it naturally to obtain a high-temperature resistant building ceramic tile.

[0013] Preferably, the preparation method of the mixed iron salt solution in step (1) is: mixing ferric chloride hexahydrate, ferric chloride tetrahydrate and pure water in a mass ratio of 1:0.37:10 for 10 minutes to obtain a mixed iron salt solution.

[0014] Preferably, the clay particle size in step (4) is 500-700 mesh.

[0015] Preferably, the sintering process parameters of step (5) are to increase the temperature to 700-760°C at a rate of 6-10°C / min and keep it for 3-5 hours, then increase the temperature to 1180-1210°C at a rate of 11-13°C / min and keep it for 2-3 hours, then increase the temperature to 1740-1780°C at a rate of 6-8°C / min and keep it for 1-3 hours, then cool down to 900-930°C and keep it for 2-3 hours.

[0016] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0017] When preparing the high-temperature resistant ceramic tile for building, the present invention comprises the following steps: firstly, vinyl-terminated amino silicone oil is reacted with 2-amino-4-pyridinemethyl mercaptan, and then reacted with 2-(diphenylphosphine)benzaldehyde to obtain modified polysiloxane; secondly, clay and a mixed iron salt solution are mixed, and coprecipitated under the action of sodium hydroxide to obtain modified clay; finally, the modified clay, magnesium trisilicate, titanium carbide, zirconium diboride, aluminum oxide and boron nitride are mixed and ground, pressed into a blank, dried and sintered, and then sprayed with the modified polysiloxane to obtain the high-temperature resistant ceramic tile for building.

[0018] Firstly, the vinyl-terminated amino silicone oil is reacted with the thiol on 2-amino-4-pyridinemethylthiol through a click reaction between the thiol and double bonds, and aminopyridine is grafted. The aminopyridine obtains a phosphorus-containing ligand through a Schiff base reaction between the amino group and 2-(diphenylphosphine)benzaldehyde; secondly, clay and a mixed iron salt solution are mixed and co-precipitated under the action of sodium hydroxide, and magnetic iron oxide particles can be generated in the subsequent high-temperature calcination process to prepare ceramic tiles; finally, the modified clay, magnesium trisilicate, titanium carbide, zirconium diboride, aluminum oxide, and boron nitride are mixed and ground, pressed into a blank, dried and sintered, and then modified. High temperature resistant building ceramic tiles obtained by spraying polysiloxane; magnesium trisilicate, titanium carbide, zirconium diboride, aluminum oxide, and boron nitride can greatly improve the high temperature resistance of ceramic tiles. The spraying of modified polysiloxane modifies the surface of the ceramic tiles with a hydrophobic layer, which can provide the ceramic tiles with good hydrophobic and self-cleaning properties. The iron particles contained in the modified clay and other components containing metal elements in the ceramic tiles can form metal ligands with the phosphorus-containing ligands in the modified polysiloxane on the surface, thereby giving the ceramic tiles photocatalytic degradation properties, which can degrade some small molecular organic matter, thereby further improving the self-cleaning ability of the ceramic tiles. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The preparation method of the mixed iron salt solution used in the following examples and comparative examples is as follows: ferric chloride hexahydrate, ferric chloride tetrahydrate and pure water are stirred and mixed at a mass ratio of 1:0.37:10 for 10 minutes to obtain a mixed iron salt solution; the clay particle size used is 500-700 mesh.

[0021] Embodiment 1:

[0022] A method for preparing a high temperature resistant ceramic tile for construction, the method comprising the following preparation steps:

[0023] (1) octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane are mixed in a mass ratio of 4:1, heated to 80°C, 0.02 times the mass of octamethylcyclotetrasiloxane and 25wt% tetramethylammonium hydroxide aqueous solution are added, the temperature is then raised to 100°C, 0.01 times the mass of octamethylcyclotetrasiloxane and 1,3-bis(aminopropyl)tetramethyldisiloxane are added, the temperature is then raised to 115°C, the reaction is continued to be heated to 140°C, the reaction is continued for 40 minutes, and then the temperature is lowered to 135°C and distilled under reduced pressure to obtain vinyl-terminated amino silicone oil;

[0024] (2) vinyl-terminated amino silicone oil, 2-amino-4-pyridinemethyl mercaptan, azobisisobutyronitrile and anhydrous toluene are mixed in a mass ratio of 1:4.1):0.1:10, and the mixture is heated to 100°C under a sealed condition, anhydrous and oxygen-free environment, and an argon atmosphere, and reacted for 2 hours. After cooling to room temperature, a 1 mol / L sodium bicarbonate aqueous solution with a volume of 4 times that of anhydrous toluene is added, and extracted with ethyl acetate. The organic phase is washed 4 times with a 1 mol / L sodium bicarbonate aqueous solution, and then washed 4 times with pure water. Finally, the pre-modified polysiloxane is obtained by rotary evaporation at 80°C for 10 minutes;

[0025] (3) Weigh pre-modified polysiloxane and 2-(diphenylphosphine)benzaldehyde in a mass ratio of 1:3, mix pre-modified polysiloxane, potassium carbonate and N,N-dimethylformamide in a mass ratio of 1:3:20, heat to 100°C and stir for 4 hours to obtain a pre-modified polysiloxane solution, mix 2-(diphenylphosphine)benzaldehyde and N,N-dimethylformamide in a mass ratio of 1:20 to obtain a 2-(diphenylphosphine)benzaldehyde solution, add the 2-(diphenylphosphine)benzaldehyde solution dropwise to the pre-modified polysiloxane solution at a dropping rate of 1 mL / min, continue to react at 100°C for 4 hours after the addition is completed, cool to room temperature, add pure water 10 times the mass of the pre-modified polysiloxane, cool to 0°C and stand for 3 hours, add acetone 3 times the mass of the pre-modified polysiloxane solution, filter and dry at 60°C for 12 hours to obtain modified polysiloxane;

[0026] (4) Clay and pure water were mixed at a mass ratio of 3:10 to obtain a clay dispersion, a mixed iron salt solution and a clay dispersion were mixed at a mass ratio of 1:2 for 7 minutes, a 10M sodium hydroxide solution of 3 times the mass of the mixed iron salt solution was added, and the mixture was stirred at a speed of 200 r / min for 60 minutes to prepare a raw material ball with a particle size of 5 mm, and the raw material ball was dried at 267 Pa and 90° C. for 12 hours to obtain a modified clay;

[0027] (5) Weigh the following raw materials by mass: 28 parts of modified clay, 7 parts of magnesium trisilicate, 9 parts of titanium carbide, 11 parts of zirconium diboride, 3 parts of aluminum oxide, and 3 parts of boron nitride; mix the above raw materials and grind them in a ball mill to obtain a powder; the ball mill speed is 200 rpm / min, and the grinding time is 6 hours; pour the powder into a mold and use a press to form a blank; the press pressure is 50 tons; place the blank in a dryer at a temperature of 280°C for drying, and then place it in a high-temperature furnace The sintering is carried out with the following process parameters: the temperature is increased to 760°C at a rate of 10°C / min and maintained for 5 hours, the temperature is then increased to 1210°C at a rate of 13°C / min and maintained for 3 hours, the temperature is then increased to 1780°C at a rate of 8°C / min and maintained for 3 hours, the temperature is then decreased to 930°C and maintained for 3 hours, to obtain a ceramic tile precursor; the modified polysiloxane is sprayed on the surface of the ceramic tile precursor, and naturally dried to obtain high temperature resistant ceramic tiles for construction.

[0028] Embodiment 2:

[0029] A method for preparing a high temperature resistant ceramic tile for construction, the method comprising the following preparation steps:

[0030] (1) octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane are mixed in a mass ratio of 4:1, heated to 80°C, 0.025 times the mass of octamethylcyclotetrasiloxane and 25 wt% tetramethylammonium hydroxide aqueous solution are added, the temperature is then raised to 100°C, 0.015 times the mass of octamethylcyclotetrasiloxane and 1,3-bis(aminopropyl)tetramethyldisiloxane are added, the temperature is then raised to 115°C, the reaction is continued to be carried out for 6 hours, the temperature is further raised to 140°C, the reaction is carried out for 40 minutes, and then the temperature is lowered to 135°C and distilled under reduced pressure to obtain vinyl-terminated amino silicone oil;

[0031] (2) Vinyl-terminated amino silicone oil, 2-amino-4-pyridinemethyl mercaptan, azobisisobutyronitrile and anhydrous toluene were mixed in a mass ratio of 1:4.15:0.2:11, and the mixture was heated to 100°C under a sealed condition, anhydrous and oxygen-free environment, and an argon atmosphere, and reacted for 2 hours. After cooling to room temperature, a 1 mol / L sodium bicarbonate aqueous solution with a volume of 4.5 times that of anhydrous toluene was added, and extracted with ethyl acetate. The organic phase was washed 3 times with a 1 mol / L sodium bicarbonate aqueous solution, and then washed 3 times with pure water. Finally, the pre-modified polysiloxane was obtained by rotary evaporation at 80°C for 7 minutes.

[0032] (3) Weigh pre-modified polysiloxane and 2-(diphenylphosphino)benzaldehyde in a mass ratio of 1:3.2, mix pre-modified polysiloxane, potassium carbonate, and N,N-dimethylformamide in a mass ratio of 1:3.2:20, heat to 95° C. and stir for 3.5 h to obtain a pre-modified polysiloxane solution, mix 2-(diphenylphosphino)benzaldehyde and N,N-dimethylformamide in a mass ratio of 1:20 to obtain a 2-(diphenylphosphino)benzaldehyde solution. liquid, adding 2-(diphenylphosphine)benzaldehyde solution to the pre-modified polysiloxane solution at a dropping speed of 1 mL / min, continuing to react at 95°C for 3.5 hours, cooling to room temperature, adding pure water 11 times the mass of the pre-modified polysiloxane, cooling to 0°C and standing for 2.5 hours, adding acetone 3.5 times the mass of the pre-modified polysiloxane solution, filtering and drying at 55°C for 12 hours to obtain modified polysiloxane;

[0033] (4) Clay and pure water were mixed at a mass ratio of 3:10 to obtain a clay dispersion, a mixed iron salt solution and a clay dispersion were mixed at a mass ratio of 1:2.5 for 7 minutes, a 10M sodium hydroxide solution of 3.5 times the mass of the mixed iron salt solution was added, and the mixture was stirred at a speed of 150 r / min for 60 minutes to prepare a raw material ball with a particle size of 5 mm, and the raw material ball was dried at 267 Pa and 90° C. for 12 hours to obtain a modified clay;

[0034] (5) Weigh the following raw materials by mass: 30 parts of modified clay, 10 parts of magnesium trisilicate, 12 parts of titanium carbide, 13 parts of zirconium diboride, 4 parts of aluminum oxide, and 3.5 parts of boron nitride; mix the above raw materials and grind them in a ball mill to obtain powder; the ball mill speed is 200 rpm / min, and the grinding time is 6 hours; pour the powder into a mold and use a press to form a blank; the press pressure is 50 tons; place the blank in a dryer at a temperature of 280°C for drying, and then place it in a high-temperature furnace The sintering is carried out with the following process parameters: the temperature is increased to 720°C at a rate of 7°C / min and maintained for 4 hours, the temperature is then increased to 1190°C at a rate of 12°C / min and maintained for 2.5 hours, the temperature is then increased to 1750°C at a rate of 7°C / min and maintained for 2 hours, the temperature is then decreased to 925°C and maintained for 2.5 hours; a ceramic tile precursor is obtained; the modified polysiloxane is sprayed on the surface of the ceramic tile precursor, and naturally dried to obtain high temperature resistant ceramic tiles for construction.

[0035] Embodiment 3:

[0036] A method for preparing a high temperature resistant ceramic tile for construction, the method comprising the following preparation steps:

[0037] (1) octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane are mixed in a mass ratio of 4:1, heated to 80°C, 0.03 times the mass of octamethylcyclotetrasiloxane and 25wt% tetramethylammonium hydroxide aqueous solution are added, the temperature is then raised to 100°C, 0.02 times the mass of octamethylcyclotetrasiloxane and 1,3-bis(aminopropyl)tetramethyldisiloxane are added, the temperature is then raised to 115°C, the reaction is continued to be carried out for 6 hours, the temperature is further raised to 140°C, the reaction is carried out for 40 minutes, and then the temperature is lowered to 135°C and distilled under reduced pressure to obtain vinyl-terminated amino silicone oil;

[0038] (2) Vinyl-terminated amino silicone oil, 2-amino-4-pyridinemethyl mercaptan, azobisisobutyronitrile and anhydrous toluene were mixed in a mass ratio of 1:4.2:0.3:12, and heated to 100°C in an argon atmosphere under sealed conditions, anhydrous and oxygen-free environment, and reacted for 2 hours. After cooling to room temperature, a 1 mol / L sodium bicarbonate aqueous solution with a volume of 5 times that of anhydrous toluene was added, and extracted with ethyl acetate. The organic phase was washed 3 times with a 1 mol / L sodium bicarbonate aqueous solution, and then washed 3 times with pure water. Finally, the pre-modified polysiloxane was obtained by rotary evaporation at 80°C for 5 minutes;

[0039] (3) Weigh pre-modified polysiloxane and 2-(diphenylphosphine)benzaldehyde in a mass ratio of 1:3.5, mix pre-modified polysiloxane, potassium carbonate and N,N-dimethylformamide in a mass ratio of 1:3.5:20, heat to 90°C and stir for 3 hours to obtain a pre-modified polysiloxane solution, mix 2-(diphenylphosphine)benzaldehyde and N,N-dimethylformamide in a mass ratio of 1:20 to obtain a 2-(diphenylphosphine)benzaldehyde solution, add the 2-(diphenylphosphine)benzaldehyde solution dropwise to the pre-modified polysiloxane solution at a dropping rate of 1 mL / min, continue to react at 900°C for 3 hours after the addition is completed, cool to room temperature, add pure water 12 times the mass of the pre-modified polysiloxane, cool to 0°C and stand for 2 hours, add acetone 4 times the mass of the pre-modified polysiloxane solution, filter and dry at 60°C for 12 hours to obtain modified polysiloxane;

[0040] (4) Clay and pure water were mixed at a mass ratio of 3:10 to obtain a clay dispersion, a mixed iron salt solution and a clay dispersion were mixed at a mass ratio of 1:3 for 5 minutes, a 10M sodium hydroxide solution of 4 times the mass of the mixed iron salt solution was added, and the mixture was stirred at a speed of 100 r / min for 60 minutes to prepare a raw material ball with a particle size of 5 mm, and the raw material ball was dried at 267 Pa and 90° C. for 12 hours to obtain a modified clay;

[0041] (5) Weigh the following raw materials by mass: 33 parts of modified clay, 11 parts of magnesium trisilicate, 14 parts of titanium carbide, 15 parts of zirconium diboride, 5 parts of aluminum oxide, and 4 parts of boron nitride; mix the above raw materials and grind them in a ball mill to obtain a powder; the ball mill speed is 200 rpm / min, and the grinding time is 6 hours; pour the powder into a mold and use a press to form a blank; the press pressure is 50 tons; place the blank in a dryer at a temperature of 280°C for drying; dry Then it is sintered in a high-temperature furnace, and the sintering process parameters are: heating to 700°C at a rate of 6°C / min and keeping for 3 hours, then heating to 1180°C at a rate of 11°C / min and keeping for 3 hours, then heating to 1740°C at a rate of 6°C / min and keeping for 1 hour, then cooling to 900°C and keeping for 2 hours to obtain a ceramic tile precursor; spraying modified polysiloxane on the surface of the ceramic tile precursor, and naturally drying to obtain high-temperature resistant building ceramic tiles.

[0042] Comparative Example 1:

[0043] The preparation method of the high temperature resistant building ceramic tile of Comparative Example 1 is different from that of Example 2 in that step (5) is modified as follows: the following raw materials are weighed by mass: 30 parts of modified clay, 10 parts of magnesium trisilicate, 12 parts of titanium carbide, 13 parts of zirconium diboride, 4 parts of aluminum oxide, and 3.5 parts of boron nitride; the above raw materials are mixed and ground by a ball mill to obtain a powder, the ball mill speed is 200 rpm / min, the grinding time is 6 hours, the powder is poured into a mold and formed into a blank by a press, and the pressure is The machine pressure is 50 tons, the blank is placed in a dryer at a temperature of 280°C for drying, and then sintered in a high-temperature furnace. The sintering process parameters are: the sintering process parameters are: heating to 720°C at a rate of 7°C / min and maintaining for 3 hours, then heating to 1190°C at a rate of 12°C / min and maintaining for 2 hours, then heating to 1750°C at a rate of 7°C / min and maintaining for 2 hours, then cooling to 925°C and maintaining for 2.5 hours; high temperature resistant building ceramic tiles are obtained.

[0044] Comparative Example 2:

[0045] The preparation method of the high temperature resistant building ceramic tile of comparative example 2 is different from that of embodiment 2 in that step (5) is modified as follows: the following raw materials are weighed by mass: 30 parts of modified clay; the above raw materials are mixed and ground by a ball mill to obtain a powder, the ball mill speed is 200 rpm / min, the grinding time is 6 hours, the powder is poured into a mold and formed into a blank by a press machine, the pressure of the press machine is 50 tons, the blank is placed in a dryer at a temperature of 280°C for drying, and after drying, it is placed in a high temperature dryer. Sintering is carried out in a furnace, and the sintering process parameters are: the temperature is increased to 720°C at a rate of 7°C / min and maintained for 3 hours, then the temperature is increased to 1190°C at a rate of 12°C / min and maintained for 2 hours, then the temperature is increased to 1750°C at a rate of 7°C / min and maintained for 2 hours, then the temperature is reduced to 925°C and maintained for 2.5 hours; a ceramic tile precursor is obtained; the modified polysiloxane is sprayed on the surface of the ceramic tile precursor, and naturally dried to obtain high-temperature resistant ceramic tiles for construction.

[0046] Tests of high temperature resistance and self-cleaning performance:

[0047] High temperature resistance test:

[0048] Test method: Referring to the standard GB / T23806-2009, the fracture toughness of the ceramic tiles prepared in the embodiment and the comparative example was tested using a C45.105 test machine. The size of the ceramic tile sample was 36mm*4mm*3mm. After being kept at 1520°C for 22 hours, the fracture toughness was tested again, and the fracture toughness retention rate was calculated. The results are shown in Table 1.

[0049] Self-cleaning performance test:

[0050] Test method: The water drop contact angle was measured using an XG-CAM contact angle meter. The results are shown in Table 1.

[0051] Table 1 Test results of high temperature resistance and self-cleaning performance

[0052] Fracture toughness retention rate (%) Contact angle (°) Example 1 96.43 Example 1 154 Example 2 96.86 Example 2 155 Example 3 97.31 Example 3 155 Comparative Example 1 57.43 Comparative Example 1 85 Comparative Example 2 52.26 Comparative Example 2 150

[0053] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the high temperature resistant building ceramic tile prepared by the present invention has good high temperature resistance and self-cleaning performance.

[0054] By comparison, the fracture toughness retention rate of Examples 1 to 3 is greater than that of Comparative Examples 1 to 2, and the contact angles of Examples 1 to 3 are greater than that of Comparative Example 1. The above test results are explained as follows: First, the vinyl-terminated amino silicone oil is subjected to a click reaction between the thiol group and the double bond and the thiol group on 2-amino-4-pyridinemethylthiol to be grafted with aminopyridine, and aminopyridine is subjected to a Schiff base reaction between the amino group and 2-(diphenylphosphine)benzaldehyde to obtain a phosphorus-containing ligand; secondly, clay and a mixed iron salt solution are mixed and coprecipitated under the action of sodium hydroxide, and magnetic iron oxide particles can be generated in the subsequent high-temperature calcination process to prepare ceramic tiles; finally, modified clay, magnesium trisilicate, and carbonized Titanium, zirconium diboride, aluminum oxide, and boron nitride are mixed and ground, pressed into blanks, dried and sintered, and then sprayed with modified polysiloxane to obtain high-temperature resistant building ceramic tiles; magnesium trisilicate, titanium carbide, zirconium diboride, aluminum oxide, and boron nitride can greatly improve the high-temperature resistance of ceramic tiles. The spraying of modified polysiloxane modifies the surface of the ceramic tiles with a hydrophobic layer, which can provide the ceramic tiles with good hydrophobic and self-cleaning properties. The iron particles contained in the modified clay and other components containing metal elements in the ceramic tiles can form metal ligands with the phosphorus-containing ligands in the modified polysiloxane on the surface, thereby giving the ceramic tiles photocatalytic degradation properties, which can degrade some small molecular organic matter, thereby further improving the self-cleaning ability of the ceramic tiles.

[0055] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A high temperature resistant building ceramic tile, characterized in that: The high temperature resistant building ceramic tile is obtained by mixing and grinding modified clay, magnesium trisilicate, titanium carbide, zirconium diboride, aluminum oxide and boron nitride, pressing them into blanks, drying and sintering them, and then spraying them with modified polysiloxane; The modified polysiloxane is obtained by reacting vinyl-terminated amino silicone oil with 2-amino-4-pyridinemethyl mercaptan and then with 2-(diphenylphosphine)benzaldehyde.

2. A method for preparing a high temperature resistant building ceramic tile, characterized in that: The method comprises the following preparation steps: (1) octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane are mixed in a mass ratio of 4:1, heated to 80°C, 0.02-0.03 times the mass of octamethylcyclotetrasiloxane is added with a 25wt% tetramethylammonium hydroxide aqueous solution, then heated to 100°C, 0.01-0.02 times the mass of octamethylcyclotetrasiloxane is added with 1,3-bis(aminopropyl)tetramethyldisiloxane, then heated to 115°C, reacted for 6h, further heated to 140°C, reacted for 40min, then cooled to 135°C and distilled under reduced pressure to obtain vinyl-terminated amino silicone oil; (2) vinyl-terminated amino silicone oil, 2-amino-4-pyridinemethyl mercaptan, azobisisobutyronitrile and anhydrous toluene are mixed in a mass ratio of 1: (4.1-4.2): (0.1-0.3): (10-12), and the mixture is heated to 100° C. in a sealed, anhydrous and oxygen-free environment under an argon atmosphere, and reacted for 2 hours. After cooling to room temperature, a 1 mol / L sodium bicarbonate aqueous solution of 4-5 times the volume of anhydrous toluene is added, and extracted with ethyl acetate, and the organic phase is washed 3-4 times with a 1 mol / L sodium bicarbonate aqueous solution, and then washed with pure water for 3-4 times. Finally, the pre-modified polysiloxane is obtained by rotary evaporation at 80° C. for 5-10 minutes; (3) Weighing pre-modified polysiloxane and 2-(diphenylphosphine)benzaldehyde in a mass ratio of 1:(3-3.5), mixing pre-modified polysiloxane, potassium carbonate, and N,N-dimethylformamide in a mass ratio of 1:(3-3.5):20, heating to 90-100° C. and stirring for 3-4 h to obtain a pre-modified polysiloxane solution, and mixing 2-(diphenylphosphine)benzaldehyde and N,N-dimethylformamide in a mass ratio of 1:20 to obtain 2-(diphenylphosphine)benzaldehyde. solution, adding the 2-(diphenylphosphine)benzaldehyde solution to the pre-modified polysiloxane solution at a dropping speed of 1 mL / min, continuing to react at 90-100°C for 3-4 hours after the dropping is completed, cooling to room temperature, adding pure water 10-12 times the mass of the pre-modified polysiloxane, cooling to 0°C and standing for 2-3 hours, adding acetone 3-4 times the mass of the pre-modified polysiloxane solution, filtering and drying at 50-60°C for 12 hours to obtain modified polysiloxane; (4) mixing clay and pure water at a mass ratio of 3:10 to obtain a clay dispersion, mixing a mixed iron salt solution and a clay dispersion at a mass ratio of 1:(2-3) for 5-10 minutes, adding a 10M sodium hydroxide solution of 3-4 times the mass of the mixed iron salt solution, stirring at a speed of 100-200 r / min for 60 minutes, preparing a raw material ball with a particle size of 5 mm, and drying the raw material ball at 267 Pa and 90° C. for 12 hours to obtain a modified clay; (5) Weigh the following raw materials by mass: 28-33 parts of modified clay, 7-11 parts of magnesium trisilicate, 9-14 parts of titanium carbide, 11-15 parts of zirconium diboride, 3-5 parts of aluminum oxide, and 3-4 parts of boron nitride; mix the above raw materials and grind them in a ball mill to obtain powder. The speed of the ball mill is 200 rpm / min, and the grinding time is 6 hours. Pour the powder into a mold and use a press to form a blank. The press pressure is 50 tons. The blank is placed in a dryer at a temperature of 280°C and dried. After drying, it is sintered in a high-temperature furnace to obtain a ceramic tile precursor; spray the modified polysiloxane on the surface of the ceramic tile precursor and dry it naturally to obtain a high-temperature resistant building ceramic tile.

3. The method for preparing a high temperature resistant ceramic tile for construction according to claim 2, characterized in that: The preparation method of the mixed iron salt solution in step (1) is as follows: ferric chloride hexahydrate, ferric chloride tetrahydrate and pure water are stirred and mixed in a mass ratio of 1:0.37:10 for 10 minutes to obtain a mixed iron salt solution.

4. The method for preparing a high temperature resistant ceramic tile for construction according to claim 2, characterized in that: The clay particle size in step (4) is 500-700 mesh.

5. The method for preparing a high temperature resistant ceramic tile for construction according to claim 2, characterized in that: The sintering process parameters of step (5) are as follows: heating to 700-760°C at a rate of 6-10°C / min and maintaining for 3-5 hours, then heating to 1180-1210°C at a rate of 11-13°C / min and maintaining for 2-3 hours, then heating to 1740-1780°C at a rate of 6-8°C / min and maintaining for 1-3 hours, then cooling to 900-930°C and maintaining for 2-3 hours.

Citation Information

Patent Citations

  • High-temperature-resistant ceramic for buildings and preparation method of high-temperature-resistant ceramic

    CN108947479A

  • Antiskid self-cleaning ceramic tile and preparation method thereof

    CN118389011A

  • Ceramic tile with photocatalysis function and preparation method thereof

    CN119019187A

  • Process for preparing new 3-(amino-phenyl-mercapto)-pyridines

    FR1268449A

  • Method of producing colored cement roof tile

    JP2003238272A